(untitled) (Sains Humanika, 2011)
This research set outs to measure Muslim culture participating by Chinese Muslim (Muallaf) through six hypothesis statements in Kuala Lumpur. It was sure that their Muslim culture applying becomes dilemma when they convert from their own religion to IslÄm. It suggests that when these converts begin to practice IslÄm, their behavior changes in line with the identity of the Malays. This is because IslÄm equates to Malay in the Malaysian context. Whilst they are welcomed by their Malay counterparts, it is nevertheless hypothesised that they may not exercise fully into the Muslim culture.